Copolymerization of polypropylene and functionalized linear α-olefin onto glass fibers - Barbosa, Silvia Elena (2001)
This work deals with a novel glass fiber surface modification and subsequent metallocenic propylene polymerization onto it. Experimental results are presented on methylaluminoxane (MAO) fixation at the fiber surface, followed by propylene-α-olefin graft copolymerization catalyzed by EtInd2ZrCl2/MAO. First results indicate that part of the produced polymer is chemically bonded to the glass fiber. Scanning electron microscopy, Fourier transform infrared spectroscopy, and X-ray disperse energy microanalysis characterization confirm the permanence of a thin polymer layer as well as aluminum and oxygen (from the MAO) on the glass surface, even after a severe solvent extraction treatment. From these results, the copolymerization of hydroxy-α-olefin, grafted on MAO pretreated glass fiber, is foreseen as a possible way to improve fiber-matrix adhesion in glass-fiber thermoplastic composites.